2020
DOI: 10.1007/s40200-020-00594-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-associated dermatological manifestations in primary care and their association with vascular complications

Abstract: Introduction Although type 2 diabetes mellitus (DM) is a global public health problem, the diabetes-associated dermatological (non-infectious) manifestations (DADM) remain poorly understood and under-diagnosed. We aimed to evaluate the prevalence of 7 known DADM in a primary care setting, and their association macro/microvascular complications. Methods Cross-sectionnal study included patients consulting in general practice for DM-follow up, from November 2016 to January 2017. Patients aged <18 years old or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In addition, in diabetes, loss of sensory innervation of the skin occurs, predisposing patients to infection and lesions [ 27 ]. Loss of neuroinflammatory signaling cells plays a determining role in the lack of healing of lower extremity ulcers [ 28 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in diabetes, loss of sensory innervation of the skin occurs, predisposing patients to infection and lesions [ 27 ]. Loss of neuroinflammatory signaling cells plays a determining role in the lack of healing of lower extremity ulcers [ 28 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lesions strongly associated with diabetes mellitus were analyzed, with a predominance of diabetic foot (19 patients), followed by necrobiosis lipoidica—7 patients, with bullosis diabeticorum and acanthosis nigricans occurring in 6 and 5 patients respectively out of 103. A study conducted by Trihan et al [ 33 ], which included 213 patients with DM shows a similar number of patients with necrobiosis lipoidica—5 patients, 4 with acanthosis nigricans and 3 with bullosis diabeticorum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…et al found a prevalence of AN of 2.3%, which corresponded to the estimated prevalence for AN among Caucasian populations. Moreover, according to the authors, in diabetic patients, AN could be an indicator of macrovascular complications, such as coronary or carotid artery disease (OR= 2.57, p < 0.05) [ 107 ].…”
Section: An and Dmmentioning
confidence: 99%
“…Scleroedema, a cutaneous mucinosis, can occur secondary to acute streptococcal throat infection, paraproteinaemia, or diabetes mellitus. The last of these, termed scleroedema diabeticorum, is thought to be due to glycosylation of collagen in the dermis leading to an excessive accumulation of collagen and mucin 12. This patient, who had a raised haemoglobin A 1c concentration of 8.9% and serum protein electrophoresis within reference limits, was treated with metformin for glycaemic control.…”
mentioning
confidence: 99%